PENGARUH GROWTH MINDSET DAN STUDENT ENGAGEMENT TERHADAP HASIL BELAJAR SISWA KELAS XI AKL SMK NEGERI 7 MEDAN - Martha Rotua Purba; Ulfa Nurhayani; Andri Zainal; Pasca Dwi Putra; Roza Thohiri (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to analyze the effects of growth mindset and student engagement on the learning outcomes of Grade XI Accounting and Financial Institution (AKL) students at SMK Negeri 7 Medan. The study was motivated by the low learning outcomes of students in the service company accounting topic. A quantitative research approach was employed, involving a population of 207 Grade XI AKL students in the 2025/2026 academic year. A sample of 136 students was selected using proportional random sampling. Data were collected through questionnaires measuring growth mindset and student engagement, as well as documentation of students’ learning outcomes. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The findings indicate that both growth mindset and student engagement have a positive and significant effect on students’ learning outcomes, with student engagement demonstrating a stronger influence. These results highlight the importance of fostering a growth mindset and encouraging active student participation in the learning process to improve academic achievement. The study implies that schools and teachers should create learning environments that support active engagement and the development of a growth mindset. This research was limited to one school and two predictor variables; therefore, future studies are recommended to involve broader samples and consider additional factors that may affect learning outcomes.